2000
DOI: 10.1002/1097-0045(20000701)44:2<118::aid-pros4>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Decreased galectin‐3 expression in prostate cancer

Abstract: BACKGROUND.Galectin-3 is a carbohydrate-binding protein whose level of expression has been shown to be correlated with metastatic potential in a number of different tumor types. The purpose of this investigation was to examine galectin-3 expression in several tumorigenic and nontumorigenic prostate cell lines and prostate tissue samples. METHODS. The expression of galectin-3 in cell lines and tissue samples was evaluated by tissue immunohistochemistry and Western blot analysis. RESULTS. Human cell lines PC-3M,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…For instance, expression of galectin-3 has been directly correlated with neoplastic potential and metastatic capacity in fibrosarcoma and melanoma cells (36) whereas Galectin-3 levels were found to be down-regulated in advanced prostate cancer (37) and colon carcinoma (38,39), when compared with their respective normal counterparts. Similarly, reduced expression of Galectin-3 has been reported in advanced histological grades of breast cancer (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, expression of galectin-3 has been directly correlated with neoplastic potential and metastatic capacity in fibrosarcoma and melanoma cells (36) whereas Galectin-3 levels were found to be down-regulated in advanced prostate cancer (37) and colon carcinoma (38,39), when compared with their respective normal counterparts. Similarly, reduced expression of Galectin-3 has been reported in advanced histological grades of breast cancer (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of course, we have to consider the possibility that gal3 deficiency might contribute to tumorigenesis regardless of NASH. Previous reports have been contradictory: some studies reported that gal3 played an important role in cancer progression and metastasis, 60–63 whereas others suggested that it was downregulated in some cancers 64–68 . The role of gal3 in tumorigenesis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA microarray and immunohistochemical experiments showed that the expression of galectin‐3 appeared to correlate with tumor indolence; being expressed predominantly in low‐grade conventional (clear cell) RCCs, indolent chromophobe RCCs, and benign oncocytomas [Young et al, 2001]. This finding is consistent with several studies showing reduced galectin‐3 expression in clinically aggressive tumors and may be relevant to the function of galectin‐3 as an adhesion molecule that inhibits metastasis [Idikio, 1998; Francois et al, 1999; Lurisci et al, 2000; Pacis et al, 2000]. Thus, galectins represent a family of molecules with a key role in RCCs progression.…”
Section: Galectins In Diagnosis and Prognosis Of Urological Malignancymentioning
confidence: 99%